2020
DOI: 10.5230/jgc.2020.20.e6
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Retrospective Analysis of Intraperitoneal Paclitaxel and Systemic Chemotherapy for Advanced Gastric Cancer with Peritoneal Metastasis

Abstract: Purpose:The objective of the present retrospective analysis was to describe the experience of intraperitoneal (IP) paclitaxel and systemic chemotherapy in patients with peritoneal metastasis (PM) of advanced gastric cancer (AGC) in a multicenter setting in Korea. Materials and Methods: The medical records of patients with AGC, who were diagnosed with PM between January 2015 and December 2018, were reviewed. IP catheter was placed in the pouch of Douglas and was used for the administration of IP paclitaxel chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…The ABSOLUTE trial showed the weekly ABX regimen had longer OS than the paclitaxel regimen (9.9 vs. 8.7 months) of peritoneal metastasis in gastric cancer patients [ 13 , 32 ]. Recently, the combination of intraperitoneal paclitaxel and systemic chemotherapy in advanced gastric cancer patients with peritoneal metastasis could enhance the OS to 20.0 months [ 33 ]. ABX following intravenous administration was thought to be infiltrated into the peritoneal tumor to the same degree as intraperitoneal injection [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ABSOLUTE trial showed the weekly ABX regimen had longer OS than the paclitaxel regimen (9.9 vs. 8.7 months) of peritoneal metastasis in gastric cancer patients [ 13 , 32 ]. Recently, the combination of intraperitoneal paclitaxel and systemic chemotherapy in advanced gastric cancer patients with peritoneal metastasis could enhance the OS to 20.0 months [ 33 ]. ABX following intravenous administration was thought to be infiltrated into the peritoneal tumor to the same degree as intraperitoneal injection [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported significant complications associated with an implanted access port and catheter system (18.3%) in a multicenter retrospective study [ 12 ]. Among these complications, abscess and infection can be fatal.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the limitations of previous studies, the perioperative IP and systemic chemotherapy for gastric cancer (PIPS-GC) study group was established in 2017 to manage AGC with PM in Korea. A multicenter retrospective study on IP chemotherapy has been performed, which showed satisfactory results [ 12 ]. Based on these results, we planned to conduct a phase I/II clinical trial.…”
Section: Introductionmentioning
confidence: 99%
“…Given that all visible tumors had to be removed to achieve complete cytoreduction, concomitant resection of visceral organs was inevitable, resulting in several serious complications. After joining the PIPS-GC study group, we discussed treatment options with other institutional researchers for patients of PM [ 19 ] and ultimately accepted the approach of patient selection based on the PCI score and patients' potential for complete cytoreduction after reflecting on the discussions. We established 2 treatment strategies based on PCI score with a cutoff value of 13 points ( Fig.…”
Section: Discussionmentioning
confidence: 99%